PENGARUH KEPADATAN KANDANG TERHADAP BOBOT HIDUP, KARKAS, DAN GIBLET BROILER UMUR 14-28 HARI DI CLOSED HOUSE - Nurul Barruni; Syahrio Tantalo; Dian Septinova; Khaira Nova (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
This study aimed to study the effect of stocking density on live weight, carcasses and giblets of broiler in closed houses; and to determine the best stocking density on live weight, carcass and giblet of broiler in a closed house. This research was conducted in April-May 2019 for 28 days with 14 days of treatments period (14-28 days) at PT. Charoen Pokphand (Kandang Bandara 2) located in Bangun Sari hamlet, Way Sari Village, Natar District, Lampung Selatan Regency. This study used a Completely Randomized Design with four treatments, of stocking density of 15 heads/m2 (P1), stocking density of 17 heads/m2 (P2), stocking density of 19 heads/m2 (P3), and stocking density of 21 heads/m2 (P4), with five replications for each treatment. The data obtained were analyzed using analysis of variance at 5% level. The result of the analysis of variance showed that the different stocking density had no significant effect on the live weight, carcasses, and giblet of broiler at 28 days of age in the closed house. Keywords: Carcass, Closed house, Giblet, Live weight, Stocking density